Let's solve the equation step by step, filling in the missing terms and providing descriptions for each operation.
-
Start with the original equation:
\( -19b + 19 = -12b + 19 \)
-
Subtract 19 from both sides:
This gives us: \[ -19b = -12b \]
-
Add 12b to both sides:
This gives us: \[ -19b + 12b = 0 \] Simplifying this, we get: \[ -7b = 0 \]
-
Divide both sides by -7:
This gives us: \[ b = 0 \]
Now let's summarize and fill in the missing descriptions:
- Start with: \( -19b + 19 = -12b + 19 \)
- Subtract 19 from both sides
- Result: \( -19b = -12b \)
- Add 12b to both sides
- Result: \( -19b + 12b = 0 \)
- Result simplifies to: \( -7b = 0 \)
- Divide both sides by -7
- Result: \( b = 0 \)
So, the missing information is:
- Add 12b to both sides
- Subtract 19 from both sides
- \( b = 0 \)
- Divide both sides by -7
Final representation: \[ b = 0 \]